Palaeobiogeography, palaeoecology and evolution of Lower Ordovician conulariids and Sphenothallus (Medusozoa, Cnidaria), with emphasis on the Fezouata Shale of southeastern Morocco - Van Iten, Heyo (2016)
The fossil record of conulariids (Cnidaria, Scyphozoa) extends downward into the topmost part of the Ediacaran System, but the first appearance of diverse, widespread conulariids is in siliciclastic rock units of Early Ordovician age, which collectively host at least six conulariid genera. Some of these same units also contain Sphenothallus, a probable medusozoan that frequently co-occurs with conulariids in Ordovician and younger deposits. Lower Ordovician conulariid localities are distributed among five (originally) Southern Hemisphere terranes, namely Core Gondwana (Archaeoconularia, Eoconularia and Teresconularia), Armorica (Conularia azaisi), Avalonia (Archaeoconularia, Eoconularia and Exoconularia), Perunica (Archaeoconularia, Conularia and Conulariella) and South China (Conulariella). C azaisi, currently known from the Southern Montagne Noire (France), probably represents a new genus. Sphenothallus occurs in South China, North China (Korea), Armorica (Southern Montagne Noire) and Core Gondwana (Morocco). In southeastern Morocco, Burgess Shale-type Konservat-Lagerstatten in the Fezouata Shale (Tremadocian Floian) yield Archaeoconularia sp., Eoconularia sp. and at least one species of Sphenothallus. This low-diversity conulariid assemblage is most similar to the Tremadocian assemblage of Wales (Avalonia), which likewise consists of a single species each of Archaeoconularia and Eoconularia. In the Fezouata Shale, Archaeoconularia sp. and Eoconularia sp. frequently occur in monospecific mass associations. Such associations probably represent an original clumped distribution on the seafloor. Additionally, some Eoconularia sp. occur in V-like pairs or radial clusters, and also some specimens were attached at the apical end to a phosphatic brachiopod or to a corner sulcus of a larger specimen of Eoconularia sp. Similar conulariid/brachiopod associations, consisting of Conularia trentonensis and Onniella sp., occur in the Upper Ordovician (Katian) Collingwood Shale of southern Ontario, Canada. (C) 2016 Elsevier B.V. All rights reserved.